Cotton tenants : three families - Agee, James, 1909-1955. (Melville House, 2013)
On assignment for "Fortune" magazine in 1936, Agee and Evans set out to explore the plight of sharecroppers during the Great Depression. Published for the first time, Agee's original dispatch (accompanied by 25 of Evans' historic photographs) is an unsparing record of three families at a desperate time.